Geometry Evaluation of Heat Transfer by Mixed Convention in Driven Cavities with Two Inserted Fins - Rocha, Luiz Alberto Oliveira; Rodrigues, Priscila M.; de Escobar, Cicero C.; dos Santos, Elizaldo Domingues; Isoldi, Liércio André (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2019)
In this work, a numerical study of a flow with heat transfer by mixed convection are carried out. The objective is the geometric evaluation through the application of the Construtal Design and the exhaustive search method. The behavior of a lid-driven cavity with stable stratification subjected to an incompressible, laminar and two-dimensional flow is investigated. The cavity has two rectangular fins inserted in the lower surface. The problem is subject to three constrains: three geometric constraints: the area of the cavity, two fin areas. The investigated geometry has three degrees of freedom: the ratio between height and cavity length (H/L) and the ratio between height and length of each fin (H1/L1 and H2/L2). The effect of the fin geometry over spatial-averaged Nusselt (NuH) is investigated for Reynolds number (ReH) = 400 and Richardson (Ri) = 0.1. The conservation equations of mass, momentum and energy are tackled with Finite Volume Method (FVM) through the use of commercial software FLUENT. The results showed that the lower H2/L2 ratios resulted in higher NuH values. An increase in NuH value of approximately 49% between the worst and the best geometrical configuration was found, thus highlighting the importance of geometric evaluation on this kind of problem. It is concluded that for the problem addressed the best behavior is obtained when the fins have a small insertion into the cavity, thus avoiding the restriction of the main vortex flow. The results found highlight the importance of the geometric evaluation for the purpose of theoretical recommendation on the geometric configurations that lead to the best thermal performance.